Case Study of POSCO: Analysis of Its Growth Strategy and Key Success Factors - Lee, Seung Joo; Lee, Eun-Hyung (Journal of Strategic Management Education, 2010)
POSCO has played a major role in Korea’s economic development by supplying domestic manufacturers with high-quality, low-cost steel products. Despite its initial disadvantage and lack of resources such as capital, technology, and raw materials, it has emerged as a world-class steel maker in a short span of time. This case study aims to explore and analyze the key success factors of POSCO through examination of the company’s growth and development process. In particular, it examines the role of government policy, top management leadership, technology learning and innovation, cost competitiveness and other factors as important drivers of success. The case also identifies its strategic challenges and key issues for growth in the future.
Keywords: Growth strategy; key success factors; steel industry; Korea